The value of performing hysteroscopy in the cases of fallopian tube obstruction during laparoscopy - Leili Hafizi; Somayeh Moeindarbari; Maliheh Amirian; Nahid Zirak; Nima Nakhaee (Mashhad University of Medical Sciences, 2021)
Introduction:  The report of fallopian tube obstruction in hysterosalpingography in infertile patients should be confirmed by laparoscopy. This study was performed with aim to assess the value of hysteroscopy in cases of fallopian tubes obstruction during laparoscopy. Methods: This interventional study was performed on 54 infertile women who were candidates for laparoscopy due to fallopian tube obstruction in Hysterosalpingography (despite normal uterine cavity) in the gynecology ward of Mashhad Imam Reza Hospital in 2014-2016. Patients were included in the study if tube obstruction was observed during laparoscopy. At the same stage, the hysteroscopy was performed, and then the status of the tubes was again checked through laparoscopy. The value of performing hysteroscopy was evaluated in terms of detecting the uterus pathology, opening of the tubes or both. Data were analyzed by SPSS software (version 20) and student t-test, Q2, and Mc-nemar tests. P<0.05 was considered statistically significant. Results: In this study, 54 patients with 74 blocked fallopian tubes were included. Hysteroscopic findings indicated intrauterine pathology in 30 cases (55.6%) and after performing hysteroscopy, at least one tube was opened in 25 cases (46.3%). 38 patients (70.4%) benefited from hysteroscopy (opening of tube or intrauterine pathology diagnosis). In the study of the relationship between hysteroscopic evidence (normal or pathologic) and consequent tube opening, the probability of tube opening was significantly higher in the pathologic cases (p<0.001). Conclusion: In the cases of observation of tube obstruction in diagnostic laparoscopy in infertile women (despite normal endometrial cavity in HSG), hysteroscopy was helpful and in many cases lead to detection of unknown uterine pathologies or help to tubal opening.